2006
DOI: 10.1098/rspb.2006.3732
|View full text |Cite
|
Sign up to set email alerts
|

The cost of replication fidelity in human immunodeficiency virus type 1

Abstract: Mutation rates should be governed by at least three evolutionary factors: the need for beneficial mutations, the benefit of minimizing the mutational load and the cost of replication fidelity. RNA viruses show high mutation rates compared with DNA micro-organisms, and recent findings suggest that the cost of fidelity might play a role in the evolution of increased mutation rates. Here, by analysing previously published data from HIV-1 reverse transcriptase in vitro assays, we show a trade-off between enzymatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 41 publications
(46 reference statements)
2
37
0
Order By: Relevance
“…Given the potential for pleiotropy among diverse gene products that has been revealed by recent genomic approaches (Paaby and Rockman, 2013;Solovieff et al, 2013), there remains a clear need for experiments testing whether mutation rate modifiers themselves have direct selective effects. Limited studies, for example, have shown that enhanced replication fidelity (lower mutation rate) may decrease replication rate in some viruses and thus be directly costly (Furio et al, 2005;Furio et al, 2007). A recent study in Pseudomonas aeruginosa also showed that a mutS mutator allele can provide inherent resistance to oxidative stress and so could have a direct fitness benefit in certain environments (Torres- Barceló et al, 2013).…”
Section: Why Aren't All Asexually Reproducing Populations Fixed For Mmentioning
confidence: 99%
“…Given the potential for pleiotropy among diverse gene products that has been revealed by recent genomic approaches (Paaby and Rockman, 2013;Solovieff et al, 2013), there remains a clear need for experiments testing whether mutation rate modifiers themselves have direct selective effects. Limited studies, for example, have shown that enhanced replication fidelity (lower mutation rate) may decrease replication rate in some viruses and thus be directly costly (Furio et al, 2005;Furio et al, 2007). A recent study in Pseudomonas aeruginosa also showed that a mutS mutator allele can provide inherent resistance to oxidative stress and so could have a direct fitness benefit in certain environments (Torres- Barceló et al, 2013).…”
Section: Why Aren't All Asexually Reproducing Populations Fixed For Mmentioning
confidence: 99%
“…Elevated mutation frequencies are associated with human pathologies such as cancer and premature aging (7,8). Large increases in accuracy, on the other hand, can be energetically costly (9) and also lead to decreased fitness.…”
mentioning
confidence: 99%
“…rspb.royalsocietypublishing.org Proc R Soc B 280: 20122047 that this has been explicitly studied in the context of viruses [29,30]. The basic principles applying to prokaryotes and eukaryotes do not directly apply to viruses because selection acts differently in viruses.…”
Section: Discussionmentioning
confidence: 99%